Home - Johnson, Tim 1961 August 27-; Parsons, Jim, 1973-; Rihanna, 1988-; Lopez, Jennifer, 1970-; Twentieth Century Fox Home Entertainment, Inc. (Los Angeles, CA Twentieth Century Fox Home Entertainment, 2015)
A lovable misfit from another planet meets a girl named Tip. The two unlikely friends embark on the greatest journey of all time.
Title from web page.
Originally released as a motion picture in 2015.
Widescreen (1.85:1).
Special features: Best party ever!; party play all mode; Ohs shake yoru boov thing ; Feel the light, Jennifer Lopez music video; Feel the light, Jennifer Lopez lyric video; Ohs boovy jukebox; Ohs party planning tips; Gallery; theatrical trailer.
Rating: PG; for mild action and some rude humor
CHV rating: G.
Keywords: Extraterrestrial beings -- Juvenile films; Interplanetary voyages -- Juvenile films; Extraterrestrial beings -- Drama; Interplanetary voyages -- Drama; DVD-Video discs; Fiction films; Feature films; Childrens films; Animated films; Video recordings for the hearing impaired; DVDs for people with visual disabilities